Konsep 'Aql Dalam Al-Qur'an Dan Neurosains - Asti Faticha Nurjanah (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2018)
In the Qur'an the term brain is not known, to illustrate the intelligence used the term of reason. The brain is the meaning of reason in the physical dimension. 'Aql is the power of thought, effort, deception, trickery, ingenuity, cunning, and the ability to see. Muslim philosophers understand 'Aql as binding, attaching, and limiting. The term 'Aql can be found in Qs. As-Syams: 7-8. Intellect is an active and conscious organ, binding and holding objects of science with words or other forms of symbolism. Neuroscience is neural science that studies the nervous system, mainly studies neurons or nerve cells with a multidisciplinary approach. Neurosains is a science that specializes in scientific studies of the nervous system. Neuroscience has traces in Islam. Islamic education has traces in the nature of neuroscience. Therefore, Islamic education can be integrated-interconnected with neuroscience.